Rural radio network recognized - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The Developing Countries Farm Radio Network (DCFRN) has been awarded the Alan Feinstein Prize for the prevention or reduction of hunger by Brown University, USA. The prize was inaugurated in 1985, and this year was ceremonially presented to...